RELASI INTERSUBJEKTIF BERSAMA ALLAH MENURUT PAULUS DALAM KOLOSE 2:6-7 - Landele, James Andris; Kumowal, Royke Lantupa (STT Ekklesia Pontianak, 2024)
Abstract: In this article, the author discusses the relationship between humans and God from the perspective of Martin Buber, a modern Jewish philosopher. Buber emphasizes the importance of the concept of intersubjective relationship (I and Thou). This concept serves as evidence that humans are relational beings and that God is referred to as an intersubjective relationship. The article employs a qualitative literature review research method. The author will gather data from various sources, such as books, literature searches, notes, and reports related to Martin Buber's views on Intersubjective Relations, and the biblical perspective on building a relationship with God according to Colossians 2:6-7. Martin Buber develops the concept of intersubjective relations through the relationships of